Climate change, disasters, and internal displacement in Asia and the Pacific : a human rights-based approach - Scott, Matthew, 1978-; Salamanca, Albert M. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines the interconnection between human agency, 'natural' disasters and climate change across ten different countries in Asia Pacific. The Asia-Pacific region accounts for the majority of global disaster-related displacement, but the experience of the millions of individuals displaced differs according to gender, age, ethnicity, (dis)ability, caste and so forth, and is dependent on the legal, administrative, social and economic structures and processes in place to support them. This book adopts a human rights approach, investigating the role of law and policy in preventing displacement, protecting people who are displaced, and engendering durable solutions across cases drawn from Thailand, Cambodia, Myanmar, Indonesia, the Philippines, China, Nepal, Bangladesh, Vanuatu and the Solomon Islands. The specific cases in the book also reflects critically on the term 'displacement', and the wider normative framework within which this phenomenon is conceptualised and addressed. The book will be of interest to researchers and practitioners working at the intersection of development, disaster risk management and climate change adaptation"--
OCLC-licensed vendor bibliographic record.
Keywords: Environmental refugees -- Asia; Environmental refugees -- Pacific Area; Global environmental change -- Social aspects -- Asia; Global environmental change -- Social aspects -- Pacific Area; SOCIAL SCIENCE / Disasters & Disaster Relief; SOCIAL SCIENCE / Third World Development